Comparison of Anterior Capsule Polishing on the Rate of Neodymium: YAG Laser Capsulotomy After Two Multifocal Intraocular Lens Implantation - Leng, Lin; Bai, Huiran; Li, Honglei; Liu, Dongle; Han, Yanfeng; Wu, Xiaoming (Frontiers in Medicine, 2022)
Purpose: To compare the impact of anterior capsule polishing (ACP) during cataract surgery on the rate of neodymium: YAG (Nd: YAG) laser capsulotomy in pseudophakic eyes with two multifocal intraocular lenses (MIOLs). Methods: Data were collected on patients who underwent cataract surgery and implanted segmental refractive MIOLs (SBL-3, Lenstec) or diffracted MIOLs (AT Lisa LISA tri 839MP, Carl Zeiss Meditec). The participants were divided into ACP and non-ACP groups based on whether the anterior capsule was polished. The primary outcome measure was whether Nd: YAG capsulotomy was performed during the three years follow-up. We used Kaplan-Meier survival curves to determine the time from IOL implantation to Nd: YAG laser capsulotomy. Results: ACP and non-ACP groups comprised 70 and 60 eyes, respectively. One year postoperatively, 7.14% of ACP group eyes and 8.33% of non-ACP group required Nd: YAG laser capsulotomy (P > 0.99). After two years, it was 24.29% and 18.33%, respectively (P = 0.52), while after three years, it reached 30.0% and 28.33% (P = 0.85). No distinct difference existed in the probability of using Nd: YAG laser in both groups evaluated using Kaplan-Meier survival curves (P = 0.81). Patients with diffractive MIOLs (AT LISA tri 839MP) implantation were more likely to require Nd: YAG laser capsulotomy (P < 0.01). Conclusion: Polishing the anterior capsule had no remarkable effect on reducing the rate of Nd: YAG laser capsulotomy following phacoemulsification in MIOLs. Patients with diffractive MIOLs implantation had a high probability of requiring Nd: YAG laser capsulotomy.